2018
DOI: 10.14207/ejsd.2018.v7n3p65
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Experimental Study of the Solar Dehydration of the Moringa Leaf and Its Potential Integration to the Sustainable Agricultural Industry

Abstract: Energy saving and environmental impact are two elements that must be considered in any sustainable process or proposal aimed at economic, social and cultural development. Moringa is a plant that has generated great interest in recent years due to its medicinal properties attributed, its leaves are an important source of food due to its high nutritional value. The plant is also used in traditional kitchens and medicinal remedies in various regions of the world. This work presents the characteristics of the dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The impact of this technique on the nutritional and organoleptic properties of the species needs to be assessed. It could also be necessary to optimize the processing duration by using solar drying equipment as it is the case for moringa leaf 33–35 . This may help processors (in most of the cases women) to save time and continue producing during the rainy season by using the sun power accumulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of this technique on the nutritional and organoleptic properties of the species needs to be assessed. It could also be necessary to optimize the processing duration by using solar drying equipment as it is the case for moringa leaf 33–35 . This may help processors (in most of the cases women) to save time and continue producing during the rainy season by using the sun power accumulators.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be necessary to optimize the processing duration by using solar drying equipment as it is the case for moringa leaf. [33][34][35] This may help processors (in most of the cases women) to save time and continue producing during the rainy season by using the sun power accumulators. Nevertheless, the overharvesting of the species is noted (Affonfere et al 13 , forthcoming) and this will lead to a problem of the sustainable use of the species.…”
Section: Processing Of Cochlospermum Spp Root and Know-how Of Producersmentioning
confidence: 99%
“…They reported that the fabricated GHD with the solar collector has the best performance in the temperature range of 40-70 • C for crop drying (Figure 10). In a study by Margarita et al [94], the drying process of moringa leaves was evaluated using different drying systems, including a GHD integrated with solar PV modules, direct open-sun-drying, and an electric oven under the climate condition of Campeche, México. The best performance for the drying process inside the GHD was achieved by providing a dried air temperature of 59 • C, resulting in a drying time of 4 h with a drop in moisture percentage of the leaves from 82.29% to 4.09%.…”
Section: Ghds Integrated With Pv Modulesmentioning
confidence: 99%
“…Figure10. Experimental setup of the GHD developed in ref [94]. with an embedded solar collector (adapted with permission).…”
mentioning
confidence: 99%
“…These leaves are rich in protein, iron, vitamin C and carotenoids (Thurber & Fahey, n.d.). Moringa leaves place major role in the food industry (Folashade et al, 2017) and the medical industry (Margarita et al, 2018) due to its extended nutrition value. The pharmacological properties of the moringa leave include hepatoprotective, antifungal, anti-ulcer, anti-bacterial etc.…”
Section: Introductionmentioning
confidence: 99%